Asymmetric larval head and mandibles of Hydrophilus acuminatus (Insecta: Coleoptera, Hydrophilidae): Fine structure and embryonic development. Issue 6 (November 2017) - Sato, Shun'ichi; Inoda, Toshio; Niitsu, Shuhei; Kubota, Souichirou; Goto, Yuji; Kobayashi, Yukimasa
Abstract: The larvae of a water scavenger beetle, Hydrophilus acuminatus, have strongly asymmetric mandibles; the right one is long and slender, whereas the left one is short and stout. The fine structure and embryonic development of the head capsule and mandibles of this species were examined using light and scanning electron microscopy, and asymmetries in shape were detected in these structures applying an elliptic Fourier analysis. The larval mandibles are asymmetric in the following aspects: whole length, the number, structure and arrangement of retinacula (inner teeth), and size and shape of both the molar and incisor regions. The larval head is also asymmetric; the left half of the head capsule is larger than the right, and the left adductor muscle of the mandible is much thicker than the right. The origin and developmental process of asymmetric mandibles were traced in developing embryos whose developmental period is about 270 h and divided into 10 stages. Mandibular asymmetries are produced by the cumulative effects of six stepwise modifications that occur from about 36% of the total developmental time onward. The significance of these modifications was discussed with respect to the functional advantages of asymmetries and the phylogeny of members of the Hydrophilidae. Highlights: Asymmetric larval mandibles of a water scavenger beetle were examined using SEM. The larval head capsule including muscles was revealed to have left-right asymmetry. The developmental process of asymmetric mandibles in embryos was examined in detail. Six stepwise asymmetric modifications in embryonic mandibles were observed. An elliptic Fourier analysis was applied for the first time to insect embryogenesis.